Suboptimal control status of young hypertensive population - Donghun Shin; JungMin Choi; Hae-Young Lee (BMC, 2023)
Abstract The prevalence of hypertension (HT) among young adults aged 18 to 39 years is estimated to be 3.7% to 8.6% worldwide. Although the prevalence of HT in young adults is lower than that of the overall population, those with HT are at substantially increased risk of cardiovascular events compared to those without HT. HT in young adults should be taken with even more caution as longer exposure to higher blood pressure leads to a higher lifetime risk of HT-mediated organ damage. However, young patients with HT show low awareness of HT compared to older patients. Also, they are more prone to show low treatment adherence despite the good efficacy of the treatment. Other risk factors that hinder HT control among young adults include alcohol intake, smoking, low physical activity, emotional stress, job stress, metabolic syndrome, and obesity. This review aimed to illustrate the suboptimal control status of the young hypertensive population and to propose strategies for improvement.